Reconceptualising Settler-Colonialism and Genocide with Special Reference to Palestine, Sri Lanka and Australia: Reflections on Damien Short's Redefining Genocide: Settler Colonialism, Social Death and Ecocide. Issue 1 (May 2017) - Docker, John
Abstract : Genocide studies are at a cross-road. In June 2016, the International Network of Genocide Scholars, sponsor of the Journal of Genocide Research, imperilled the future of genocide studies by aligning itself with Zionist Israel, which many scholars consider to be a genocidal settler-colonial perpetrator state. Almost at the same time, Damien Short's important intervention Redefining Genocide was published, suggesting new directions for genocide studies in the Anthropocene and featuring Palestine as one of its case studies. In considering historical and ongoing genocides in Palestine, Sri Lanka, and Australia, Redefining Genocide inspires a rethinking of the relationship between genocide, settler-colonialism, and the state.